Investigation of Plasmonic Detection of Human Respiratory Virus. Issue 7 (8th June 2020) - Das, Chandreyee Manas; Guo, Yan; Kang, Lixing; Ho, Ho‐pui; Yong, Ken‐Tye
Abstract: The COVID‐19 virus has been recently identified as a new species of virus that can cause severe infections such as pneumonia. The sudden outbreak of this disease is being considered a pandemic. Given all this, it is essential to develop smart biosensors that can detect pathogens with minimum time delay. Surface plasmon resonance (SPR) biosensors make use of refractive index (RI) changes as the sensing parameter. In this work, based on actual data taken from previous experimental works done on plasmonic detection of viruses, a detailed simulation of the SPR scheme that can be used to detect the COVID‐19 virus is performed and the results are extrapolated from earlier schemes to predict some outcomes of this SPR model. The results indicate that the conventional Kretschmann configuration can have a limit of detection (LOD) of 2E‐05 in terms of RI change and an average sensitivity of 122.4 degRIU −1 at a wavelength of 780 nm. Abstract : The entire world is fighting a major public health crisis in the form a unique viral disease, caused by a coronavirus that has been named COVID‐19. In this work, a theoretical study of a plasmonic sensing scheme in the form of simulations that can be used to detect the COVID‐19 virus is presented.